Assessing the Outcomes of Organizational Politics on Employees Work Behaviors - Rughoobur, Soujata (2021)
This paper attempts to assess the outcomes of organizational politics on employees as organizational politics has been identified by various studies to give rise to employees being constantly demotivated, dissatisfied and lack of productiveness in the workplace. Factors like job satisfaction, organizational commitment, motivation and turnover intentions have been identified as potential resulting factors of organizational politics. An online survey method was used for the data collection and the questionnaire was sent to 300 employees. A response rate of (N = 144) was obtained. Findings revealed that organizational politics affects positively turnover intentions of employees and decreases the level of employees’ job satisfaction. Organizational politics was positively related to employee motivation and a non-significant relationship was obtained for the relationship between organizational politics and organizational commitment. This study is expected to help both practitioners and scholars to tackle the issue of organizational politics in the workplace as employees remain the main capital of the business which has to be well managed.